Multiplex real-time PCR diagnostic of relapsing fevers in Africa. - Haitham Elbir; Mireille Henry; Georges Diatta; Oleg Mediannikov; Cheikh Sokhna; Adama Tall; Cristina Socolovschi; Sally J Cutler; Kassahum D Bilcha; Jemal Ali; Dayana Campelo; Steven C Barker; et al. (Public Library of Science (PLoS), 2013)
BACKGROUND:In Africa, relapsing fever borreliae are neglected arthropod-borne pathogens causing mild to deadly septicemia and miscarriage. The closely related Borrelia crocidurae, Borrelia duttonii, Borrelia recurrentis and Borrelia hispanica are rarely diagnosed at the species level, hampering refined epidemiological and clinical knowledge of the relapsing fevers. It would be hugely beneficial to have simultaneous detection and identification of Borrelia to species level directly from clinical samples. METHODOLOGY/PRINCIPAL FINDINGS:We designed a multiplex real-time PCR protocol targeting the 16S rRNA gene detecting all four Borrelia, the glpQ gene specifically detecting B. crocidurae, the recN gene specifically detecting B. duttonii/B. recurrentis and the recC gene specifically detecting B. hispanica. Compared to combined 16S rRNA gene and flaB gene sequencing as the gold standard, multiplex real-time PCR analyses of 171 Borrelia-positive and 101 Borrelia-negative control blood specimens yielded 100% sensitivity and specificity for B. duttonii/B. recurrentis and B. hispanica and 99% sensitivity and specificity for B. crocidurae. CONCLUSIONS/SIGNIFICANCE:The multiplex real-time PCR developed in this study is a rapid technique for both molecular detection and speciation of relapsing fever borreliae from blood in Africa. It could be incorporated in point-of-care laboratory to confirm diagnosis and provide evidence of the burden of infection attributed to different species of known or potentially novel relapsing fever borreliae.